Myanmar national spectrum management policy: Is it best practice? - Thaw Tar Min; Elizabeth Fife; Erik Bohlin (International Telecommunications Society (ITS), 2014)
Over the past decade, several debates on spectrum management regimes in the developed countries have been held. However, the spectrum management regimes of developing countries are relatively understudied, especially east-developed countries. This paper studies current spectrum management reform in Myanmar. Myanmar has pursued reform of its telecommunication sector over the past two years. The initial round of reform resulted in the issuing of two nationwide telecom-operating licenses, followed by development of a regulatory policy framework to promote competition. Yet, the development of the country's regulatory policy is still on going. In terms of spectrum management, spectrum is regulated and allocated by the Department. At present, valuable spectrum is critically under-utilized in Myanmar. As part of the allocation of licenses to other operators, a clear allocation of spectrum is important in enabling cost and time efficient provision of services to the market. Therefore, the need for a transparent spectrum policy, that is, monitoring, identifying spectrum that is already in use, and protection of assigned frequencies still needs development. As a greenfield market, Myanmar has the opportunity to benefit from an improved use of its spectrum and to adopt efficient spectrum management policies. This paper will review three basic approaches for spectrum management regime, study the current spectrum management reform in Myanmar, offer policy recommendations and provide implications for future research on spectrum management and related areas. The findings show that Myanmar government had been using obsolete policies for ages. Until recent two years, major policy changes were happened. In addition, the spectrum management reform in Myanmar is going through a transition from the government-based approach to the market-based approach. Liberalized spectrum management policies have been issued, but not yet put into action. Hence, the study argues that the government should have a strong, committed regulatory environment in place before embarking on a transition in order to facilitate the transition process. Finally, this study provides further studies on liberalization, the digital divide, the development of telecom and broadband policy and specific reform in Myanmar.
Keywords: 330; spectrum management; policy; liberalization; Myanmar